Chemical synthesis of new histone deacetylase inhibitors and their evaluation as anticancer agents - Diana O. Silva (2019)
"Epigenetics and its key role in gene expression have become increasingly important in cancer research. Histone proteins play an important role in gene expression control through modifications like acetylation, phosphorylation and methylation. Histone deacetylases (HDAC) can regulate expression levels via acetylation of lysine residues of histone proteins.(...)"